Steam turbine rotor discs failure evaluation and repair process implementation. (October 2015) - Mazur, Zdzislaw; Hernandez-Rossette, Alejandro
Highlights: The presence of sodium on crack surfaces is indicative of caustic-induced stress-corrosion. The intergranular crack initiation and propagation is typical of a SCC failure mechanism. The Stress Corrosion Crack factor and humid ambient of operation is indicative of stress corrosion. The success of the rotor operation relied heavily on a specialized welding technique. Abstract: Two rotor discs failed in a 84-MW unit installed in a power plant. The failure was evidenced by large circumferential fractures of blades attachments in both discs. Disc failure was evaluated by investigating rotor operation history, steady state stress analysis by finite element (FEA), disc fracture surface fractography and deposit evaluation. It was found that this disc failure was driven by stress corrosion due to significant static stresses, humid ambient operation and disc material susceptibility. To correct disc failure and restore turbine original characteristics, a disc welding repair procedure was developed. This repair process was implemented and rotor discs restored by weld deposition, post weld heat treatment and machining. As a result, the rotor was returned to service and its useful life extended.